Nitrogen mineralization of bioslurry and other manures in soil - Haque, M Asadul; Jahiruddin, M; Rahman, M Mazibur; Saleque, M Abu (Research in Agriculture Livestock and Fisheries, 2015)
The experiment was conducted to examine the nitrogen (N) mineralization pattern of bioslurry and other manures under aerobic and anaerobic soil conditions. Two bioslurries (cowdung and poultry manure) and their original manures (cowdung and poultry manure) @ 3, 5, 10 and 20 t ha-1, respectively, were thoroughly mixed with soil and incubated in aerobic and anaerobic moisture condition for 12 weeks and available N (both NH4+-N and NO3--N) was measured by steam distillation method. NO3--N was the dominant form of inorganic N in aerobic soil, whereas, NH4+-N dominated under anaerobic soil condition. When highest cumulative total available N mineralization among the manures at 3, 5, 10 and 20 t ha-1 rate was considered after 12 weeks of incubation, the N mineralization was 5.0, 5.5, 6.8 and 4.3 times higher, respectively, in aerobic condition over anaerobic condition. Under aerobic condition cowdung bioslurry and poultry manure bioslurry had very closer percentage of N mineralization and was much higher compared to their original manure (cowdung and poultry manure, respectively). With the increase of the rate of manure application, total available N release was increased but percent N release was rather decreased irrespective of the types of manure and soil moisture contents. Application of bioslurries in parallel with their original manures (cowdung and poultry manure) in soils are, therefore, should be considered and recommended to increase N fertility in soil. Res. Agric., Livest. Fish.2(2): 221-228, August 2015